Connecting coast and inland: Perforated marine and freshwater snail shells in the Croatian Mesolithic - Komšo, Darko; Vukosavljević, Nikola (2011)
Perforated shells figure prominently in discussions of exchange systems and body ornamentation during the Mesolithic in Europe. This paper discusses assemblages of perforated marine (Columbella rustica) and freshwater (Lithoglyphus naticoides) snail shells recovered from recent excavations of Mesolithic sites in Croatia. Numerous finds occur in several sites in Istria on the Adriatic coast and at Zala cave in the inland region of Lika, suggesting the possible existence of an exchange or trading system. Several other Mesolithic sites withperforated marine and freshwater snail shells are omitted from this discussion because these sites are located on the Adriatic coast, therefore suggesting local production of perforated snail shells. The probable existence of a Mesolithic regional exchange system between coastal and inland areas is supported by the presence of exotic shells, both on the coast and inland. Comparison of metric attributes (shell size and size of perforation) and the morphology of perforations in each group suggest similar treatment of snail shells found in Istria and in Lika. Mesolithic specimens were compared only with modern examples of C. rustica because modern populations of L. naticoides have not yet been found. This comparison suggests either strong selectivity during the Mesolithic in favour of larger specimens, or changed environmental circumstances. Future research should explore if Lithoglyphus naticoides, found in Mesolithic, still exists today
Projekt MZOS
ENG